Hubungan Suami Perokok Dengan Terjadinya Bayi Berat Badan Lahir Rendah Di RSUD Sidoarjo - Alif Isroaini; Nursaidah (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2019)
Sulawesi in Indonesia, especially in the south most of the 79.2% were low birth weight in term pregnancies. This is caused by misuse of smoking is often done. Cigarette smoke contains over 4000 chemicals in cigarettes by 20 species of which are carcinogenic and toxic ingredients found in tobacco smoke a lot. The purpose of this study to determine the relationship of husband and smokers with low birth weight in Sidoarjo Hospital. This type of research is the use of analytical case-control study design. Independent variable is the husband of smokers and the occurrence of low birth weight is the dependent variable. The study population was all infants born incidence in Sidoarjo District Hospital with a population of 20 and 20 LBW BBLN in a month ie on 23 May-23 June 2012 by using primary and secondary data, the study sample using probability sampling with a purposive sampling, this study used data analysis techniques in a way that the data processing Editing, Coding, Scoring, Tabulating. Chi-square teststatistic (X2) with α = 0.05. From the result showed that a minority with a very heavy smoker category husband of 20 respondents (50%). Minority of respondents in the category of LBW by 20 respondents (50%). Based on the results of statistical tests by using a manual with the chi square test (X2) with α = 5% with 3 dk X2 table value 7,81 which count 8 > 7,81 then the value dk rejected h1 ho accepted means there is a relationship of husband and smokers LBW in Sidoarjo Hospital. The conclusion of the study is affecting your relationship smokers LBW incidence is caused by toxins found in cigarette smoke that causes damage and is carcinogenic. Need for additional information dangers of smoking and secondhand smoke especially for the mother to the fetus health professions in addition to the need for additional education on the dangers of secondhand smoke to pregnant women during ANC visits.